Twitter Public Sentiment on Fintech by Using Drone Emprit - Muhammad Zulva Zeta Zaidan; Muhammad Mujtahid; Aam Slamet Rusydiana (SMART Insight, 2022)
Public trust is the main key to the success of a company's product. Businesses can find out how much their products are trusted by the community through reviews as well as various public opinions that are poured on social media. This research aims to map the sentiments of people in the world towards Fintech recorded on social media platforms Twitter. The results of this study are that people show negative sentiment towards fintech. as much as 9,324 mentions negative twitter users and as many as 2,708 mentions positive towards fintech. The fintech industry especially in Indonesia, in this case, needs to respond well to things that are weaknesses so that public trust can be earned.